2002
DOI: 10.1046/j.1365-2672.2002.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivity of manual and automated immunomagnetic separation methods for detection of Shiga toxin-producing Escherichia coli O157:H7 in milk

Abstract: Aim: To determine the sensitivity of methods for detection of injured and uninjured Escherichia coli O157:H7 (E. coli O157) in raw and pasteurized milk. Methods and Results: Raw milk, pasteurized milk with 1AE5% fat content and pasteurized milk with 3AE5% fat content were spiked with E. coli O157 at low levels. The samples were enriched in modified tryptone soya broth with novobiocin (mTSBn) at 37°C. Aliquots of the enriched culture were analysed either by manual immunomagnetic separation (MIMS) and culturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…For the isolation of VTEC O26 and O111 strains, including the recovery of stressed cells from a variety of foods, Drysdale et al (2004) found that incubation at 42°C in BPW alone and BPW supplemented with 8 mg l )1 vancomycin gave better results than mTSB + n . By comparison, Reinders et al (2002) showed that detection of injured and uninjured E. coli O157 in raw or pasteurized milk following direct enrichment in mTSB + n was superior to BPW, although both media were incubated at 37°C in their study so it is not possible to draw a direct comparison with findings reported by Drysdale et al (2004).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For the isolation of VTEC O26 and O111 strains, including the recovery of stressed cells from a variety of foods, Drysdale et al (2004) found that incubation at 42°C in BPW alone and BPW supplemented with 8 mg l )1 vancomycin gave better results than mTSB + n . By comparison, Reinders et al (2002) showed that detection of injured and uninjured E. coli O157 in raw or pasteurized milk following direct enrichment in mTSB + n was superior to BPW, although both media were incubated at 37°C in their study so it is not possible to draw a direct comparison with findings reported by Drysdale et al (2004).…”
Section: Discussionmentioning
confidence: 88%
“…By comparison, Reinders et al (2002) showed that detection of injured and uninjured E. coli O157 in raw or pasteurized milk following direct enrichment in mTSB + n was superior to BPW, although both media were incubated at 37°C in their study so it is not possible to draw a direct comparison with findings reported by Drysdale et al (2004). The optimal growth temperature of 20 E. coli O157 and 12 non-O157 VTEC strains in Mueller-Hinton broth was reported by Gonthier et al (2001) to be 40AE2 and 41AE2°C, respectively.…”
Section: CL Baylismentioning
confidence: 93%
“…In this study, the detection limit of CTC-FISH is 10 4 cells/ml by the use of the frame spotting method (12). Combination with concentration techniques, for example, filtration or immunomagnetic separation, which has been described for the detection of bacteria with a high recovery rate (22,25), should improve the limit. In addition, epifluorescence microscopy is a major tool for the direct detection of bacteria and was also used in this study.…”
mentioning
confidence: 84%
“…First, there are no commercial IMS beads available for serogroups 045 and 0121. IMS has been shown to be an A 32 32 21 30 23 14 20 B 32 32 18 32 29 18 32 C 32 30 26 22 27 20 32 Total 96 effective and important tool for the isolation of STEC bacteria, especially E. coli 0157:H7 strains, from complex sample matrices, including bovine feces (19), soils (16), milk (27), and ground beef (2,33). Second, the background flora and/or other serogroups competed with each other either in the enrichment medium or on the chromogenic agar plate.…”
Section: 3 =>* <=Oulmentioning
confidence: 99%